The Role of Strategic Intelligence in Achieving Competitive Advantag"A Field Study On Unipharma Pharmaceutical Company in Damascus Rural" (Damascus University Journal for the economic and Political sciences, 2025)
The Study Aimed to Demonstrate Strategic Intelligence's Role in Achieving Competitive Advantage Through a Research on Unipharma Pharmaceutical Industries, In This Context, The Researcher Used the Descriptive Approach by Using a Simple Random Sample Which Was Distributed to /61/ Employees, And Obtained /35/ Questionnaires Which Met the Analysis Requirements, With 57% Recovery Rate.The Study Reached Various Results, And The Most Important Were: The Strategic Intelligence Dimensions’ Impact (Systems Logic Thinking, Future Vision) Among The Managers Of Uniphrma Company And Between Achieving The Company’S Competitive Advantage, And Also The Absence Of Significant Differences On Strategic Intelligence’S Role (Future Vision, Systems Logic Thinking) In Achieving The Competitive Advantage Of Uniphrma Company (Scientific Specialization, Age), The Study Recommended Strengthening Work To Achieve And Maintain The Competitive Advantage of Unipharma to be a Sustainable Competitive Advantage In The Long Run, By Maintaining Quality and Speed in Meeting Customers, and Working to Keep Pace With Renewable Technological and Environmental Changes, By Conducting Training Courses for Individuals Working In The Company On Programs. New Technology That Serves Customers in an Advanced, More Distinctive and Modern Way.
Keywords: Strategic Intelligence; Future Vision; Systems Thinking; Foresight; Partnership; Creativity; Competitive Advantage